2010
DOI: 10.1080/01140671.2010.511126
|View full text |Cite
|
Sign up to set email alerts
|

A highly efficient in vitro plant regeneration andAgrobacterium-mediated transformation ofBrassica oleraceavar.botrytis

Abstract: A highly efficient in vitro plant regeneration and Agrobacterium-mediated transformation of Brassica oleracea var. botrytis A reliable and efficient regeneration protocol from the cotyledons and hypocotyls is successfully established using three cauliflower genotypes. Thidiazuron (TDZ) is found to be an effective inducer of shoot formation. Both the hypocotyl and cotyledon segments are highly responsive (100%) to shoot formation and produce a maximum of 15.8 shoots per hypocotyl explant on MS salts with B 5 vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 37 publications
1
0
0
Order By: Relevance
“…Chakrabarty et al (2002) reported maximum transformation frequency (evidenced by GUS staining) of 22.6%. A similar range of transformation efficiencies was reported by Yu and co-workers in 2010 (21.6% and 18.3% for cotyledons and hypocotyls). In such context our protocol assures at least 2.5 fold increase in frequency of genetic modification (and more than sixfold increase when compared only to R. rhizogenes -mediated transformation).…”
Section: Discussionsupporting
confidence: 88%
“…Chakrabarty et al (2002) reported maximum transformation frequency (evidenced by GUS staining) of 22.6%. A similar range of transformation efficiencies was reported by Yu and co-workers in 2010 (21.6% and 18.3% for cotyledons and hypocotyls). In such context our protocol assures at least 2.5 fold increase in frequency of genetic modification (and more than sixfold increase when compared only to R. rhizogenes -mediated transformation).…”
Section: Discussionsupporting
confidence: 88%